Endometriosis - Fernandes, Martiniano (2015)
It should be considered as "Endometriosis" all ectopic respond to specific hormonal stimulation. Adenomyosis or "Endometriosis" intra mural as pelvic or at any other location were appreciated as a single condition, however, and different sites of origin. The incidence of "Endometriosis" in Brazil, it is generally much lower than in the countries of North America. This is due in part to the lack of systematic reviews of all surgical specimens, as well as due to the habit of Brazilian women (North least) to marry very young, about 18 years and 30 has already had to 6-8 children.